Optimized CRISPR/Cas9 strategy for homology-directed multiple targeted integration of transgenes in CHO cells - Shin, Sung Wook; Lee, Jae Seong (Biotechnology and Bioengineering, 2020)
Site-specific integration has emerged as a promising strategy for precise Chinese hamster ovary (CHO) cell line engineering and predictable cell line development (CLD). CRISPR/Cas9 with the homology-directed repair (HDR) pathway enables precise integration of transgenes into target genomic sites. However, inherent recalcitrance to HDR-mediated targeted integration (TI) of transgenes results in low targeting efficiency, thus requiring a selection process to find a targeted integrant in CHO cells. Here, we explored several parameters that influence the targeting efficiency using a promoter-trap-based single- or double-knock-in (KI) monitoring system. A simple change in the donor template design by the addition of single-guide RNA recognition sequences strongly increased KI efficiency (2.9–36.0 fold), depending on integration sites and cell culture mode, compared to conventional circular donor plasmids. Furthermore, sequential and simultaneous KI strategies enabled us to obtain populations with ~1–4% of double-KI cells without additional enrichment procedures. Thus, this simple optimized strategy not only allows efficient CRISPR/Cas9-mediated TI in CHO cells but also paves the way for the applicability of multiplexed KIs in one experimental step without the need for sequential and independent CHO–CLD procedures.
Keywords: Chinese hamster ovary; Chinese Hamster ovary cells; CRISPR/Cas9; double cut donor; Monitoring system; Optimized strategies; Precise integration; Template designs; Animals; CHO Cells; Clustered Regularly Interspaced Short Palindromic Repeats; Cricetulus; CRISPR-Cas Systems; Gene Knock-In Techniques; Plasmids; RNA, Guide; Transgenes; Chinese hamster ovary (CHO); CRISPR/Cas9; double cut donor; homology-directed repair; multiple knock-in; targeted integration